UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA BIOLOGI MELALUI METODE CERAMAH PLUS TANYA JAWAB DAN TUGAS (CPTT) - Ari Joko Triyono (Bioedukasi Jurnal Pendidikan Biologi, 2013)
Based on the result of observation is gotten about the condition of the class when learning procces, the conditions are: there are some students do not do assigment, do not give respon when the teacher ask to the student, do not have confident to ask about the material to the teacher, and do not give attention when the teacher gives explanation. So the learning procces tobe pasif. The result of learning is not good, this is can be seen from the students that pass only 37,5%. While the school give the grade of KKM 72. The aim of  this research is to know the improvement of activity  and the result of  student biology learning by using CPTT method. The subject of this research is the students at seventh grade of SMP Negeri 2 Batanghari that consist of 38 students. Based on the result of research, all activity aspec have done  by the student.Student expressed complete ( assess > 72) at cycle I equal to 60,53% and at cycle II increase  become 84,21%. Thereby method CPTT can improve the learning activity and biology learning achievement. Kata Kunci: Metode CPTT, Aktivitas Belajar, Hasil Belajar Biologi.